Shaping the Infant Microbiome With Non-digestible Carbohydrates - Verkhnyatskaya, Stella; Ferrari, Michela; de Vos, Paul; Walvoort, Marthe T. C. (Frontiers in Microbiology, 2019)
Natural polysaccharides with health benefits are characterized by a large structural diversity and differ in building blocks, linkages and lengths. They contribute to human health by functioning as anti-adhesives preventing pathogen adhesion, stimulate immune maturation and gut barrier function, and serve as fermentable substrates for gut bacteria. Examples of such beneficial carbohydrates include the human milk oligosaccharides (HMO). Also, specific non-digestible carbohydrates (NDCs), such as galacto-oligosaccharides (GOS) and fructo-oligosaccharides (FOS) are being produced with this purpose in mind, and are currently added to infant formula to stimulate the healthy development of the newborn. They mimic some functions of HMO, but not all. Therefore, many research efforts focus on identification and production of novel types of NDCs. In this review, we give an overview of the few NDCs currently available (GOS, FOS, polydextrose), and outline the potential of alternative oligosaccharides, such as pectins, (arabino)xylo-oligosaccharides, and microbial exopolysaccharides. Moreover, state-of-the-art techniques to generate novel types of dietary glycans, including sialylated GOS and galactosylated chitin, are presented as a way to obtain novel prebiotic NDCs that help shaping the infant microbiome.